Implementasi Kebijakan Pengawasan Sungai Oleh Dinas Lingkungan Hidup Kabupaten Minahasa - Rantung, Margareth I. R.; Mantiri, Jeane; Pontoh, Mutiara Maria; Polii, E. H. (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to learn to analyze and describe the Implementation of Surveillance Policy by the Environmental Services of Minahasa District. The research method used is descriptive dermatative. The number of informants in this study is five. Data collection using observation, interview and documentation techniques. Data analysis through Data Reduction, Data Presentation and Conclusion Drawing. The results of the research show that the Programme of Action: the program of cleaning up the toubeke river is only carried out by the plumage and depletion. Here DLH contributes to the transportation of garbage. DLH provides fleet/facilitating vehicles and involves several officers. In 2023, he's already done twice a garbage cleaning program on the toubeke river. Executives: No special units have been assigned from the Environmental Services, adding that this lack of skilled personnel clearly constitutes an obstacle to enforcing supervisory functions. Results: From surveillance seen by DLH the toubeke river is still dirty These problems arise, among other things, because the laws made by the government are less stringent so that the people do not obey or do not perform as they ought to be as already laid down in the law.